Analisis Dampak Akuisisi: Implikasi Terhadap Harga Saham, Struktur Modal dan Nilai Perusahaan (Studi Empiris : Perusahaan Akuisisi Yang Terdaftar di Komisi Pengawas Persaingan Usaha Periode 2019-2023) - Rani, Dewi; Septian, Defel; Nabila, Fitri; Khairunnisa; Cahyani, Arie (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to examine and analyze the impact of acquisitions on stock prices, capital structure, and firm value of companies registered with the Competition Supervisory Commission during the 2019-2023 period. This research is a quantitative study with a comparative approach. The sample was determined using the purposive sampling method, resulting in 12 companies as the research sample. Stock prices were measured using an event study, capital structure was measured using solvency ratios, and firm value was measured using the Tobin’s Q ratio. The research data consisted of stock price data and annual report data. This study employed the Wilcoxon Signed-Rank Test for data analysis. The results indicate that stock prices, capital structure, and firm value do not show significant differences before and after the acquisition.